The Role of the National Land Agency in Resolving Land Parcel Exchange Disputes through Mediation: A Case Study in Pekalongan Regency - Tuljanah, Nadia (Universitas Islam Negeri Sumatera Utara, 2026)
Land registration in Indonesia aims to ensure legal certainty and protection of land rights, as regulated under the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997. However, in practice, administrative errors such as the exchange of land parcels in certificates still frequently occur, leading to legal uncertainty and disputes within the community. This study examines the role of the National Land Agency (BPN) in resolving such disputes through mediation, with a case study conducted in Pekalongan Regency. The research employs a normative-empirical approach by analyzing statutory regulations, official documents, and field data. The findings indicate that BPN holds a strategic role in mediating disputes, verifying physical and juridical data, and correcting administrative errors in land certificates. Nevertheless, several challenges persist, including limited human resources, low public legal awareness, and the restricted administrative authority of BPN. Strengthening institutional capacity, improving data accuracy, and enhancing inter-agency coordination are necessary to optimize mediation outcomes. Overall, effective mediation by BPN contributes to orderly land administration, the reduction of agrarian conflicts, and the realization of legal certainty in Indonesia’s land sector.